Adapting the Sustainable Development Goals and the New Urban Agenda to the city level: Initial reflections from a comparative research project. Issue 1 (2nd January 2019) - Valencia, Sandra C.; Simon, David; Croese, Sylvia; Nordqvist, Joakim; Oloko, Michael; Sharma, Tarun; Taylor Buck, Nick; Versace, Ileana
ABSTRACT: The Sustainable Development Goals and the New Urban Agenda recognise the role of cities in achieving sustainable development. However, these agendas were agreed and signed by national governments and thus implementing them at the local level requires a process of adaptation or localisation. In this paper, we analyse five aspects that practitioners and researchers need to consider when localising them: (1) delimitation of the urban boundary; (2) integrated governance; (3) actors; (4) synergies and trade-offs and (5) indicators. These considerations are interrelated, and while not exhaustive, provide an important initial step for reflection on the challenges and opportunities of working with these global agendas at the local level. The paper draws on the inception phase of an international comparative transdisciplinary research project in seven cities on four continents: Buenos Aires (Argentina), Cape Town (South Africa), Gothenburg (Sweden), Kisumu (Kenya), Malmö (Sweden), Sheffield (UK) and Shimla (India).